Non-destructive Testing and Repair of Pipelines - Barkanov, Evgeny N., editor 655999; Dumitrescu, Andrei, editor 656000; Parinov, Ivan A., 1956-, editor 656002 (Cham : Springer, 2018)
This book describes efficient and safe repair operations for pipelines, and develops new methods for the detection and repair of volumetric surface defects in transmission pipelines. It also addresses the physics, mechanics, and applications of advanced materials used for composite repair of corroded pipelines. Presenting results obtained in the European Commission's INNOPIPES FRAMEWORK 7 programme, it develops long-range ultrasonic and phased array technologies for pipeline diagnostics, and explores their interactions with discontinuities and directional properties of ultrasonic antenna array. The book subsequently shares the results of non-destructive testing for different types of materials applications and advanced composite repair systems, and characterizes the mechanical properties by means of fracture methods and non-destructive techniques. In turn, the book assesses the currently available technologies for reinforcement of pipelines, drawing on the experience gained by project partners, and evaluates the recovery of the carrying capacity of pipeline sections with local corrosion damage by means of analytical and numerical procedures. It develops an optimization method based on the planning of experiments and surface techniques for advanced composite repair systems, before validating the numerical models developed and experimentally gauging the effectiveness of composite repair with the help of full-scale hydraulic tests